Maternal satisfaction in health facilities during childbirth and Newborn survival in Bihar State of India - Sandhya R. Mahapatro; Mayadhar Sethy (Discover Public Health)
Abstract India has made significant strides in reducing neonatal mortality rate (NMR) from 52 per 1000 live births in 1990 to 20 per 1000 live births in 2020. Nevertheless, the decline is not uniform across the states including Bihar the state of India. Even though Bihar has seen a considerable increase in institutional deliveries, a crucial health intervention to reduce NMR, the decline is gradual with 21 per 1000 live births in 2020, accounting almost 78% of infant deaths. This underscores the disparities in standard of care provided at health facilities which could have an adverseimpact on NMR. Using a mixed method approach in eight selected districts of Bihar, the present study explores mothers’ satisfaction through care provided in facilities and examines the association between maternal satisfaction from the quality of services and neonatal survival. The study finds that improved quality of institutional care is significantly associated with lower neonatal deaths. The study also identifies gaps in providing quality care, including long waiting times, inappropriate staff behavior, and provision of poor postnatal care. Addressing these gaps through appropriate policy measures is essential to accelerate progress towards reducing neonatal mortality in the state and achieving the Sustainable Development Goals. Efforts to improve the public health system in Bihar should prioritize enhancing the quality of services to ensure better maternal and neonatal outcomes.